The Study of Raw Water Turbidity Removal in Sedimentation Unit Continuous Discharges Flow (CDF) Method Using Plate Settlers - Ridwan, Ridwan; Afrianita, Reri; Hadi, Refa Nabila (Andalasian International Journal of Applied Science, Engineering and Technology, 2022)
The sedimentation unit using the continuous discharges flow (CDF) method can remove raw water turbidity of 91.09% with initial turbidity of 75.248 NTU. The performance of the sedimentation unit using the CDF method needs to be tested at high turbidity, which is more than 100 NTU. Sedimentation using the CDF method with the addition of plate settlers is an alternative that can be done by increasing the turbidity value. This study aims to determine the performance of the sedimentation unit using the CDF method with the addition of plate settlers in the removal of high turbidity. The study used a laboratory-scale reactor of 240 L/hour, with units consisting of plunge coagulation, baffle channel flocculation and a 5% CDF method sedimentation unit with plate settlers. The study used artificial raw water with variations in turbidity of 110.355 NTU, 132.035 NTU, and 153.338 NTU. The research shows that the efficiency of removal of turbidity on average for the variation of turbidity is 92.32%, 91.25%, and 89.87%, respectively. The correlation value and significance of Rank Spearmen from the variation of turbidity to reactor performance are -0.926 and 0.00, respectively. In other words, the more turbid the raw water, the lower the reactor performance